In Memoriam: Zbandut Inna Semenovna, literary editor of the "Ophthalmological Journal" (Ukrainian Journal of Ophthalmology, 2025)
On February 19, 2022, Inna Semenovna Zbandut, literary editor of the Journal of Ophthalmology (Ukraine), Candidate of Biological Sciences, passed away. All her work is inextricably linked with the Filatov Institute and with the Journal of Ophthalmology (Ukraine). Inna Semenovna lived an interesting life; she was distinguished by true intelligence, education, literacy, high professionalism, zest for life and optimism.Inna Semenovna Zbandut (née Soldatenko) was born on August 17, 1931, in Kharkiv; her father, Semion Ste-panovich, was a forest engineer, and her mother, Valentina Efimovna, a typist. Inna Semenovna’ father was trans-ferred to work to the Odessa Forestry District in 1933, and since that time her life has been closely associated with the South Palmira.